Design and implementation of an automated office environment system using embedded sensors - Anil Kumar; Sanket S Naik Dessai; Shivaprasad Yadav (Institute of Advanced Engineering and Science, 2022)
Office automation is the process using machines with the help of embedded computing perform the office activities and its tools and applications. The office automated using computer-aided processing stored, visual and audio data to simplify, improve, and automate the power saving and time management of the organization. A very important component of office automation concerns the automation of employee centred activities such as authentication, automatic alerting of appointments and automatic powering on/off personal computer. The employee image is captured using Java media framework, attendance records for all employees is gathered and processed automatically, and they can be accessed from the database on a monthly or weekly basis. The various software and hardware components of the system were developed and integrated to form the Exypnos Office System and validated on real life scenarios. Java proved to be a versatile platform for implementing a project of this nature with diverse requirements. Web camera interfacing and image capturing are implemented in the Java environment with the help of Java media framework (JMF). Java short message service (SMS) application programming interface (API) and Bluetooth technology is used for sending schedules through SMS. Radio frequency identification (RFID) systems use many different frequencies, but the most common and widely used and supported by our reader is 125 kHz. Office automation systems have more benefits to an organization. The project is implemented on MS Windows platform and in future can be implemented in Linux platform.